Productive Robots and Industrial Employment: The Role of National Innovation Systems - Chrystalla Kapetaniou; Christopher A. Pissarides (Institute of Labor Economics (IZA), 2022)
In a model with robots, and automatable and complementary human tasks, we examine robot-labour substitutions and show how it they are influenced by a country's "innovation system". Substitution depends on demand and production elasticities, and other factors influenced by the innovation system. Making use of World Economic Forum data we estimate the relationship for thirteen countries and find that countries with poor innovation capabilities substitute robots for workers much more than countries with richer innovation capabilities, which generally complement them. In transport equipment and non-manufacturing robots and workers are stronger substitutes than in other manufacturing.
Keywords: J23; L60; O33; O52; 330; robots-employment substitution; automatable tasks; complementary task creation; innovation environment; industrial allocations